2003
DOI: 10.1085/jgp.200308899
|View full text |Cite
|
Sign up to set email alerts
|

Stretch of β1 Integrin Activates an Outwardly Rectifying Chloride Current via FAK and Src in Rabbit Ventricular Myocytes

Abstract: Osmotic swelling of cardiac myocytes and other types of cells activates an outwardly rectifying, tamoxifen-sensitive Cl− current, ICl,swell, but it is unclear whether Cl− currents also are activated by direct mechanical stretch. We tested whether specific stretch of β1-integrin activates a Cl− current in rabbit left ventricular myocytes. Paramagnetic beads (4.5-μm diameter) coated with mAb to β1-integrin were applied to the surface of myocytes and pulled upward with an electromagnet while recording whole-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
126
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(136 citation statements)
references
References 75 publications
10
126
0
Order By: Relevance
“…5F). 96 Data suggest that integrin stretching may contribute to a mechano-electric feedback in the heart by modulating electrical activity. In a vascular endothelial cell model, integrin-linked magnetic beads were used to demonstrate that the transduction of local mechanical forces into biological signals is mediated through the activation of focal adhesion sites.…”
Section: Activation Of Mechanotransduction Receptors and Mechano-sensmentioning
confidence: 99%
“…5F). 96 Data suggest that integrin stretching may contribute to a mechano-electric feedback in the heart by modulating electrical activity. In a vascular endothelial cell model, integrin-linked magnetic beads were used to demonstrate that the transduction of local mechanical forces into biological signals is mediated through the activation of focal adhesion sites.…”
Section: Activation Of Mechanotransduction Receptors and Mechano-sensmentioning
confidence: 99%
“…Gramicidin was added as indicated by the arrow to ensure high cation permeability, i.e., to establish conditions where the rate of RVD is dictated by the Cl -permeability. cardiac ventricular myocytes is shown to regulate VRAC, 38 it is likely that inhibition of RVD by integrin b 1 knockdown in ELA cells involves inhibition of VRAC. VRAC current can in most cell types be activated under conditions with strongly buffered intracellular Ca 2C .…”
Section: Biophysical Characterization Of Vracmentioning
confidence: 99%
“…9D), (iv) sensitivity to membrane potential (VSOAC inhibited by depolarization / VRAC shows outward rectification and varying degree of inactivation at positive potentials 7 ), and (v) regulation via integrin b 1 , i.e., VSOAC is unaffected by integrin b 1 knockdown 37 whereas VRAC is activated by integrin b 1 stretch. 34,38,92 Variation in stoichiometry of LRRC8 components and their regulation / localization to subdomain in the plasma membrane could explain differences between VSOAC and VRAC activities (see below).…”
Section: Volume-sensitive Organic Anion Transporters -Vsoacmentioning
confidence: 99%
“…A number of groups have demonstrated that integrins regulate potassium, calcium, or chloride fluxes either indirectly (17)(18)(19)(20)(21)(22) or directly (19, 21, 23, 26 -28). Vitronectin, but not fibrinonectin or laminin, selectively affects potassium currents in an Arg-Gly-Asp sequence-dependent manner in developing mouse hippocampal neurons (29).…”
mentioning
confidence: 99%
“…It is found in the cytosol in cells-at-rest but is associated with the cell membrane following a hypotonic challenge. Thus, physiological cell swelling stimulates cytosol to membrane transposition of ICln (21). However, controversy arises over this hypothesis (38).…”
mentioning
confidence: 99%